(untitled) (Research, Society and Development, 2022)
Objective: to analyze, through an integrative review, the literature findings on the impacts of SARS-CoV-2 infection on pregnancy. Methodology: this is a descriptive study, characterized as an integrative literature review. It was established as the guiding question of the study: what are the impacts of COVID-19 on pregnancy? For this, PubMed, MedLine, Lilacs and Scielo databases were consulted. Results: the main impacts of COVID-19 on pregnancy were found: severe clinical evolution of the population of pregnant women in relation to non-pregnant women; the development of “cytokine storm”; findings of poor maternal and/or fetal perfusion; fibrin deposition and intense recruitment of inflammatory infiltrates; longest periods of and greatest graves; increased mechanical admission to the Intensive Care Unit, need for ventilation, increased accessibility rates and delayed deliveries; Depression, anxiety and problems developed during and after pregnancy. The risk of death was observed and the addition in the level of physical activity to the social cycle, isolation led to the anguish of anguish and the preoccupation with the course of death. Final Considerations: The impact of COVID-19 on pregnancy goes beyond the biological phenomenon of the disease, also on the psychological and emotional state of pregnancies. In this sense, the development of more important studies are essential to unveil the dynamism of the disease in the maternal population, promoting actions in the future.